Heavy-metal contents in oysters (Crassostrea gigas) cultivated on the southeastern coast of the Gulf of California, Mexico - Góngora-Gómez, Andrés Martín; García-Ulloa, Manuel; Muñoz Sevilla, Norma Patricia; Domínguez-Orozco, Ana Laura; Villanueva-Fonseca, Brenda Paulina; Hernández-Sepúlveda, Juan Antonio; Ortega Izaguirre, Rogelio (HIDROBIOLÓGICA, 2017)
Background. For its flesh and flavor, the Pacific oyster Crassostrea gigas is cultivated worldwide, but as filter feeders, this bivalve bioaccumulates heavy metals from different pollution sources, rendering them unsafe for human consumption. Goals. We carried out this study to assess the heavy metal concentrations in cultivated oysters from a farm located on the southeastern coast of the Gulf of California during 2011. Methods. Oyster samples were analyzed monthly (March- December 2011) for cooper (Cu), cadmium (Cd), chromium (Cr), nickel (Ni), lead (Pb), zinc (Zn), arsenic (As), and mercury (Hg). Results. The mean values (?g g-1, dry weight) for each metal were Cu = 51.42 ± 25.92, Cr = 24.97 ± 32.38, Cd = 13.84 ± 4.22, Ni = 10.26 ± 12.18, Pb = 2.18 ± 1.28, As = 0.37 ± 0.08, Zn = 267.42 ± 92.29, and Hg = 0.02 ± 0.01. Conclusions. The results suggest that metal burdens could be influenced by anthropogenic activities such as agriculture and aquaculture surrounding the culture zone. Cu, Cr, Cd, and Pb levels (?g g-1, fresh weight) were above the maximum permissible values and thus pose a threat to human health. Metal concentrations must be monitored periodically.